2019
DOI: 10.15835/buasvmcn-asb:0015.19
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Characterization of the Probiotic Properties of a Bacterial Strain for Used in Monogastric Nutrition

Abstract: This study aimed to evaluate some probiotic properties of Bacillus subtilis ATCC 6051a. The phenotypic profile, resistance to pH by simulated gastric juice (pH 2 and 3), bile salts by simulated intestinal fluid, survivability (%), heat and antibiotics tolerance were investigated. The strain is a Gram-positive, rod-shaped bacteria, arranged in short chains or in small irregular pairs with the ability to produce spores. Good viability at pH 2 and 3, with a survival of more than ≥80%, was found. In the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…(2013) found that BS can secrete pathogen-suppressive substances that have bacteriostatic action on common pathogens such as Staphylococcus aureus and E. coli which were highly sensitive to sample concentrate, and the bacteriostatic effect is equivalent to normal antibiotics. Therefore, our results suggest that the dietary inclusion of BS (ATCC 6051a strain) based on in vitro enzyme production profiles ( Dumitru et al., 2019 ) contributed to enhance performance and bone quality as well as improve GIT microbial balance in broiler consuming SBM and CWP diets.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…(2013) found that BS can secrete pathogen-suppressive substances that have bacteriostatic action on common pathogens such as Staphylococcus aureus and E. coli which were highly sensitive to sample concentrate, and the bacteriostatic effect is equivalent to normal antibiotics. Therefore, our results suggest that the dietary inclusion of BS (ATCC 6051a strain) based on in vitro enzyme production profiles ( Dumitru et al., 2019 ) contributed to enhance performance and bone quality as well as improve GIT microbial balance in broiler consuming SBM and CWP diets.…”
Section: Discussionmentioning
confidence: 89%
“…These results support the previous reports that other strains of BS, or a probiotic with a predominance of BS, improved BWG and FCR of broiler chicks ( Jeong and Kim, 2014 ; Li et al., 2016 ; Gao et al., 2017 ; Mahmoud et al., 2017 ; Zhen et al., 2018 ; Flores et al., 2019 ). The reasons for the improvement in BWG and FCR of broilers fed a BS probiotic supplement were probably because of the increased FI or to the ability to produce some extracellular enzymes such as amylase, protease, and lipase ( Dumitru et al., 2019 ) that improved nutrient digestibility. Another possible reason is that Bacillus spp .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacteria determined from intestinal microflora were incubated aerobically at 37 C for 48 h. Escherichia coli (E. coli; biotype b-hemolytic) and Salmonella spp. was analysed as reported by Dumitru et al (2019). The viable counts of Lactobacillus spp.…”
Section: Microbiological Analysesmentioning
confidence: 99%